Wnt5a signaling mediates biliary differentiation of fetal hepatic stem/progenitor cells in mice12. Issue 6 (14th May 2013) - Kiyohashi, Kei; Kakinuma, Sei; Kamiya, Akihide; Sakamoto, Naoya; Nitta, Sayuri; Yamanaka, Hideto; Yoshino, Kouhei; Fujiki, Junko; Murakawa, Miyako; Kusano‐Kitazume, Akiko; Shimizu, Hiromichi; Okamoto, Ryuichi; et al.
Abstract The molecular mechanisms regulating differentiation of fetal hepatic stem/progenitor cells, called hepatoblasts, which play pivotal roles in liver development, remain obscure. Wnt signaling pathways regulate the development and differentiation of stem cells in various organs. Although a β‐catenin–independent noncanonical Wnt pathway is essential for cell adhesion and polarity, the physiological functions of noncanonical Wnt pathways in liver development are unknown. Here we describe a functional role for Wnt5a, a noncanonical Wnt ligand, in the differentiation of mouse hepatoblasts. Wnt5a was expressed in mesenchymal cells and other cells of wild‐type (WT) midgestational fetal liver. We analyzed fetal liver phenotypes in Wnt5a‐deficient mice using a combination of histological and molecular techniques. Expression levels of Sox9 and the number of hepatocyte nuclear factor (HNF)1β+HNF4α− biliary precursor cells were significantly higher in Wnt5a‐deficient liver relative to WT liver. In Wnt5a‐deficient fetal liver, in vivo formation of primitive bile ductal structures was significantly enhanced relative to WT littermates. We also investigated the function of Wnt5a protein and downstream signaling molecules using a three‐dimensional culture system that included primary hepatoblasts or a hepatic progenitor cell line. In vitro differentiation assays showed that Wnt5a retarded the formation of bile duct–like structures in hepatoblasts, leading instead to hepatic maturation of such cells. Whereas Wnt5a signaling increased steady‐state levels of phosphorylated calcium/calmodulin‐dependent protein kinase II (CaMKII) in fetal liver, inhibition of CaMKII activity resulted in the formation of significantly more and larger‐sized bile duct–like structures in vitro compared with those in vehicle‐supplemented controls. Conclusion: Wnt5a‐mediated signaling in fetal hepatic stem/progenitor cells suppresses biliary differentiation. These findings also suggest that activation of CaMKII by Wnt5a signaling suppresses biliary differentiation. (HEPATOLOGY 2013;)